2015
DOI: 10.1007/jhep06(2015)077
|View full text |Cite
|
Sign up to set email alerts
|

Soft theorems from effective field theory

Abstract: The singular limits of massless gauge theory amplitudes are described by an effective theory, called soft-collinear effective theory (SCET), which has been applied most successfully to make all-orders predictions for observables in collider physics and weak decays. At tree-level, the emission of a soft gauge boson at subleading order in its energy is given by the Low-Burnett-Kroll theorem, with the angular momentum operator acting on a lower-point amplitude. For well separated particles at tree-level, we prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
151
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 101 publications
(153 citation statements)
references
References 220 publications
(520 reference statements)
2
151
0
Order By: Relevance
“…For the operators involving one ultrasoft gluon and two collinear quarks, we have the basis g us (q) n (q)n : The helicity selection rules act different for the two projections of the B us fields due to the different definition of helicity in the two cases. The Wilson coefficients of the operators that include B us(n)0 can be related to the Wilson coefficients of the leading power operators using RPI symmetry (see [66]). In particular, we have…”
Section: Jhep11(2017)142mentioning
confidence: 99%
See 4 more Smart Citations
“…For the operators involving one ultrasoft gluon and two collinear quarks, we have the basis g us (q) n (q)n : The helicity selection rules act different for the two projections of the B us fields due to the different definition of helicity in the two cases. The Wilson coefficients of the operators that include B us(n)0 can be related to the Wilson coefficients of the leading power operators using RPI symmetry (see [66]). In particular, we have…”
Section: Jhep11(2017)142mentioning
confidence: 99%
“…In [66] it was shown that in the general case of N jets, certain subleading operators involving B a us(n)± are generated by the RPI expansion of the leading power operator. However, these particular operators vanish for the case of back to back jets that we consider here.…”
Section: Jhep11(2017)142mentioning
confidence: 99%
See 3 more Smart Citations